2003
DOI: 10.1021/jp027002l
|View full text |Cite
|
Sign up to set email alerts
|

Three-Color Three-Laser Photochemistry of Di(p-methoxyphenyl)methyl Chloride

Abstract: Three-color three-laser photochemistry of di(p-methoxyphenyl)methyl chloride ((p-CH 3 OC 6 H 4 ) 2 CHCl ) An 2 CHCl) was studied by three-step excitation using 308-, 355-, and 495-nm lasers with delay times of 100 ns to 3 µs. Di(p-methoxyphenyl)methyl radical (An 2 CH • ) was produced together with An 2 CH • in the excited state (An 2 CH • *) and di(p-methoxyphenyl)methyl cation (An 2 CH + ) in quantum yields of 0.09, 0.12, and 0.12, respectively, after a laser flash during 308-nm laser (first laser) photolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…These materials are expected to find uses in various applications, such as in memory devices in the IT field, as sensor materials for light modulation, or in the industrial field as well as in textile products (printed shirts). Due to the poor solubility of this DE in water, we used the inclusion effect of cyclodextrins (CDs) to dissolve it in water, after which we investigated its photoionization properties [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], which is a type of photolysis. The photochromic behavior of diarylethene derivatives attached to CD and dissolved in water has been reported to influence the quantum yield of the transformation from an open to a closed structure [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…These materials are expected to find uses in various applications, such as in memory devices in the IT field, as sensor materials for light modulation, or in the industrial field as well as in textile products (printed shirts). Due to the poor solubility of this DE in water, we used the inclusion effect of cyclodextrins (CDs) to dissolve it in water, after which we investigated its photoionization properties [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], which is a type of photolysis. The photochromic behavior of diarylethene derivatives attached to CD and dissolved in water has been reported to influence the quantum yield of the transformation from an open to a closed structure [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Photochemistry with laser radiation is a promising tool to broaden the application spectrum of miniaturized systems, by facilitating a powerful activation step due to a wide range of available wavelengths and energy ranges [2930]. Moreover, the optical systems can be designed in a way that the reaction initiation by photons and an additional online analysis of the running reaction is feasible.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of photons, which are delivered via a suitable light-transparent window, on the processes running in miniaturized photoreactors, is investigated with a focus on increasing the yield and selectivity as well as decreasing the reaction time. Photochemistry with laser radiation is a promising tool to broaden the application spectrum of miniaturized systems, by facilitating a powerful activation step due to a wide range of available wavelengths and energy ranges [ 29 30 ]. Moreover, the optical systems can be designed in a way that the reaction initiation by photons and an additional online analysis of the running reaction is feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Two-color two-laser and the three-color three-laser flash photolysis techniques have been successfully applied to open new photochemical reactions, , where the transient intermediates, such as various aromatic molecules in the lowest singlet and triplet excited states, radicals, cations, and radical cations generated from the first or second laser flash photolysis, are selectively excited with the second or third laser irradiation to give those intermediates in the excited states, leading to new reactions such as unimolecular decompositions and isomerization, bimolecular energy, and electron transfer. ,, We have also reported that the enhancement of the yield of di(4-methoxyphenyl)methyl cation was achieved by the second 355-nm laser irradiation at an appropriate timing, through the resonant two-photon ionization (TPI) of di(4-methoxyphenyl)methyl radical generated from the first 308-nm laser irradiation, during the 308-, 355-, and 532-nm three-color three-laser flash photolysis of di(4-methoxyphenyl)methyl chloride …”
Section: Introductionmentioning
confidence: 99%
“…22,23,[31][32][33][34] We have also reported that the enhancement of the yield of di(4-methoxyphenyl)methyl cation was achieved by the second 355-nm laser irradiation at an appropriate timing, through the resonant two-photon ionization (TPI) of di(4-methoxyphenyl)methyl radical generated from the first 308-nm laser irradiation, during the 308-, 355-, and 532-nm three-color three-laser flash photolysis of di(4-methoxyphenyl)methyl chloride. 5 The TPI of organic compounds proceeds through two-step excitation from the S 0 to S 1 states and from the S 1 to S n states. 35 The photoionization probability of the TPI depends on the electronic character of the S 1 and S n states, which depends on the substituent of S and has influence on the properties of S(S 1 ) and S(S n ), and the electronic conformation of the radical cations.…”
Section: Introductionmentioning
confidence: 99%